Navigating the Future: AI, Floods, Politics, and Entrepreneurship in Management Operations for Resilient Societies in Jakarta - Solehudin, Heri; Darmayanti, Rani; Agustin, Faikotul Wulan; Santoso, Citra Reksi (CV. Bimbingan Belajar Assyfa, 2025)
This research investigates the integration of artificial intelligence (AI), flood risk management, political dynamics, and entrepreneurship in enhancing resilient city management in Jakarta from 2013 to 2023. Jakarta faces significant challenges due to rapid urbanization, climate change, and political instability, making it highly susceptible to flooding. Over the past decade, the frequency and intensity of floods have escalated, affecting over 1.5 million residents each year. Contributing factors include inadequate infrastructure, inconsistent public policies, and limited resources. The study employs a mixed-methods approach, incorporating a comprehensive literature review and analysis of 50 relevant case studies. This analysis reveals trends in AI adoption, the impact of political dynamics, and the role of entrepreneurship in flood management. Quantitative data establishes correlations between AI adoption rates and flood management effectiveness, while qualitative insights explore the influence of political factors and entrepreneurial innovations. Findings indicate that AI has improved flood prediction accuracy by up to 30%, enabling faster responses. Additionally, entrepreneurial initiatives, such as app-based flood monitoring and community infrastructure projects, play a crucial role in resilience. However, political instability often hinders the implementation of these solutions. Ultimately, the research emphasizes the need for collaboration among the government, private sector, and communities to strengthen disaster resilience, highlighting the synergy of technology, policy, and innovation in facing future challenges.